PENGENDALIAN LARVA NYAMUK Culex pipiens DENGAN EKSTRAK BIJI SRIKAYA (Annona squamosa L) - Evie Lutfiah; Indra Wirawan; Sriwulan Sriwulan (Prodi Biologi Universitas PGRI Ronggolawe, 2024)
The Culex pipiens mosquito is one of the insects that carries diseases, especially filariasis. Mosquito control can be done using insecticides, either in the form of mosquito coils, electricity, or anti-mosquito lotion. However, the safety of insecticides on the market needs to be questioned because they contain chemicals. Therefore, alternative methods based on natural ingredients are needed, one of which is srikaya seeds. Therefore, this research was carried out to measure the biolarvicidal activity of sugar apple seed extract against Culex pipiens mosquito larvae. This research is an experimental study with treatment in the form of a concentration of srikaya seed extract, consisting of 0%, 3%, 6%, 9%, 12% and 15% with 3 repetitions. The data obtained was the average number of Culex pipiens mosquito larvae that died as a result of the treatment given. The percentage of larval death data was then calculated and the data was analyzed statistically using one-way anova with calculations using SPSS 23 software. The results of the study showed that differences in the concentration of sugar apple seed extract had a significant influence on the mortality of Culex pipiens mosquito larvae, where a concentration of 15% gave the highest average larval death. but not significantly different from concentrations of 12%, 9%, and 6%.